1997
DOI: 10.1093/emboj/16.21.6414
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the pp72syk protein tyrosine kinase by platelet integrin alpha IIbbeta 3

Abstract: pp72syk is essential for development and function of several hematopoietic cells, and it becomes activated through tandem SH2 interaction with ITAM motifs in immune response receptors. Since Syk is also activated through integrins, which do not contain ITAMs, a CHO cell model system was used to study Syk activation by the platelet integrin, alpha IIb beta 3. As in platelets, Syk underwent tyrosine phosphorylation and activation during CHO cell adhesion to alpha IIb beta 3 ligands, including fibrinogen. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 104 publications
8
149
1
2
Order By: Relevance
“…In this respect, although DR-mediated signals activate Syk, cytoplasmic domains of DR␣ and DR␤ chains are devoid of ITAM motif. Likewise, the IL-2 receptor (30), CD29 (59), and platelet integrin ␣ IIb ␤ 3 (60) are also capable of activating Syk, although these receptors carry no ITAM motif in their cytoplasmic domains. Because Syk was not co-precipitated with DR molecules in our study (data not shown), certain molecules associated with DR may play a role in activating Syk, which are currently under investigation, using mass mapping techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, although DR-mediated signals activate Syk, cytoplasmic domains of DR␣ and DR␤ chains are devoid of ITAM motif. Likewise, the IL-2 receptor (30), CD29 (59), and platelet integrin ␣ IIb ␤ 3 (60) are also capable of activating Syk, although these receptors carry no ITAM motif in their cytoplasmic domains. Because Syk was not co-precipitated with DR molecules in our study (data not shown), certain molecules associated with DR may play a role in activating Syk, which are currently under investigation, using mass mapping techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese hamster ovary (CHO) cell lines that stably express human wild-type or mutant ␣IIb␤3 have been described (11)(12)(13). The amount of ␤3 integrin expressed on the surface of these cell lines was equivalent, as assessed by flow cytometry by using a ␤3-specific antibody.…”
Section: Methodsmentioning
confidence: 99%
“…However, platelets can adhere to and be activated by a fibrinogen-coated surface (42), so there must be a recognition potential even in the "nonactivated" conformation. Clustering of GPIIb-IIIa leads to activation of p72 SYK without obvious Fc␥ involvement; however, the mechanism for this is not yet known (43). Aggretin clustering of ␣ 2 ␤ 1 and GPIb appears to induce a similar signaling pathway that may be common to several integrins.…”
Section: Figmentioning
confidence: 98%